The Differential Role of Human Cationic Trypsinogen (PRSS1) p.R122H Mutation in Hereditary and Nonhereditary Chronic Pancreatitis: A Systematic Review and Meta-Analysis - Cheng Hu; Li Wen; Lihui Deng; Chenlong Zhang; Aurelia Lugea; Hsin-Yuan Su; Richard T. Waldron; Stephen J. Pandol; Qing Xia (Gastroenterology Research and Practice)
Background. Environmental factors and genetic mutations have been increasingly recognized as risk factors for chronic pancreatitis (CP). The PRSS1 p.R122H mutation was the first discovered to affect hereditary CP, with 80% penetrance. We performed here a systematic review and meta-analysis to evaluate the associations of PRSS1 p.R122H mutation with CP of diverse etiology. Methods. The PubMed, EMBASE, and MEDLINE database were reviewed. The pooled odds ratio (OR) with 95% confidence intervals was used to evaluate the association of p.R122H mutation with CP. Initial analysis was conducted with all etiologies of CP, followed by a subgroup analysis for hereditary and nonhereditary CP, including alcoholic or idiopathic CP. Results. A total of eight case-control studies (1733 cases and 2415 controls) were identified and included. Overall, PRSS1 p.R122H mutation was significantly associated with an increased risk of CP (OR = 4.78[1.13–20.20]). Further analysis showed p.R122H mutation strongly associated with the increased risk of hereditary CP (OR = 65.52[9.09–472.48]) but not with nonhereditary CP, both alcoholic and idiopathic CP. Conclusions. Our study showing the differential role of p.R122H mutation in various etiologies of CP indicates that this complex disorder is likely influenced by multiple genetic factors as well as environmental factors.